Shift of innervation zone location with different levels of isometric contractions in biceps brachii muscle - Piitulainen, H.; Rantalainen, T.; Linnamo, V.; Komi, P.; Avela, J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
It is assumed, that isometric contraction stabilizes the conditions for surface electromyography (sEMG) measurements. As mentioned in the SENIAM guidelines (Hermens et al. 1999), this assumption is met, if the sEMG electrodes are not placed over the innervation zone (IZ). IZ corresponds to the area where the individual neuromuscular junctions are concentrated and can be located with surface electrode arrays (Masuda and Sadoyama 1986). Martin and MacIsaac (2006) have shown that in the biceps brachii muscle (BB) shift in IZ can take place with changes in joint angle. This shift could disturb the sEMG signals in dynamic conditions if the sEMG electrode is placed near the IZ. Whether this is the case also in different isometric contraction levels is not clear at present. Therefore, the purpose of the present study was to determine the stability of IZ with multiarray sEMG in different isometric contraction levels in BB. Isometric maximal voluntary contraction (MVC) was first determined for the elbow flexors of the dominant arm at elbow angle of 120o for 14 male subjects. Thereafter the subjects performed submaximal isometric contractions (8 s) with 10%, 20%, 30%, 40%, 50% and 75% of MVC. SEMG signals were recorded with a multiarray electrode (13 x 5, 8 mm inter-electrode distance, LISiN-OT Bioelectronica, Torino, Italy) from the short head of BB. Monopolar sEMG signals were amplified with a bandwidth of 10-750 Hz and sampled at 2048 Hz. Signals were post-processed to bipolar signals and adjacent channels were plotted for five columns to determine the location of IZ (by reversal in signal polarity in two adjacent channels or low amplitude in a single channel). IZ location results were normalized with respect to 10% MVC level. IZ shift to proximal direction was between 0 and 2.8 cm depending on the subject and investigated column. The mean shift of all the columns was 0.8 ± 0.5 cm (10% vs. 100% MVC, p < 0.001). IZ stability was increased in the medial direction since no shift was present in the most medial column. Shift in IZ location with increasing isometric contraction level could be explained by shortening of the muscle fibers and lengthening of the tendon and intramuscular connective tissue due to increasing load. There seems to be a spatial dependency in this relationship, probably due to anatomical round shape of BB. Another explanation could be uneven force transmission or load distribution in the muscle. Current results underline the importance of individual investigation of IZ location(s) before the placement of sEMG electrodes. With this procedure, misleading results in sEMG experiments due to subject dependency in IZ location(s) and its shift due to muscle activity could be avoided.